2009
DOI: 10.1038/onc.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between GLI and JUN enhances transcription of JUN and selected GLI target genes

Abstract: Sustained Hedgehog (HH) signaling is implicated in basal cell carcinoma of the skin and other types of cancer. Here we show that GLI1 and GLI2, the main transcriptional activators of the HH pathway, directly regulate expression of the activator protein 1 (AP-1) family member JUN, a transcription factor controlling keratinocyte proliferation and skin homeostasis. Activation of the JUN promoter by GLI is dependent on a GLI-binding site and the AP-1 sites known to be involved in self-activation of JUN. Transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 81 publications
2
49
0
Order By: Relevance
“…Koga et al, 2008;Kasperczyk et al, 2009). Expression of Gli1 is reported to be regulated by TGFb, Ras, JUN, SCL/TAL1 and EWS-FLI1 oncoprotein (Ji et al, 2007;Kasai et al, 2008;Zwerner et al, 2008;Beauchamp et al, 2009;Laner-Plamberger et al, 2009;NolanStevaux et al, 2009). The interaction between PKC and hedgehog signaling varies depending on PKC isoforms and cell types.…”
Section: Interactions Between Hedgehog Signaling and Other Pathwaysmentioning
confidence: 99%
“…Koga et al, 2008;Kasperczyk et al, 2009). Expression of Gli1 is reported to be regulated by TGFb, Ras, JUN, SCL/TAL1 and EWS-FLI1 oncoprotein (Ji et al, 2007;Kasai et al, 2008;Zwerner et al, 2008;Beauchamp et al, 2009;Laner-Plamberger et al, 2009;NolanStevaux et al, 2009). The interaction between PKC and hedgehog signaling varies depending on PKC isoforms and cell types.…”
Section: Interactions Between Hedgehog Signaling and Other Pathwaysmentioning
confidence: 99%
“…In addition to Gli1, Itch is involved in the regulation of c-Jun and other targets . Recently, a cooperation between c-Jun and Gli1 has been described in human keratinocytes, in which Hh enhances the expression of c-Jun, thus synergizing with it for cell cycle progression (Laner-Plamberger et al, 2009). To rule out the possibility that c-Jun regulates MB growth by targeting AP-1, we tested whether a cross-talk between Gli1 and c-Jun also exists in MB cells.…”
Section: Itch-dependent Degron Is Required For the Control Of The Oncmentioning
confidence: 99%
“…12 Further, Gli2 can upregulate c-jun through that same specific binding site. When Gli2 and c-jun bind to their respective sites concurrently, there is synergistic upregulation of c-jun.…”
Section: Introductionmentioning
confidence: 99%
“…Laner-Plamberger et al 12 reported their findings of the molecular interface between Gli and c-jun in immortalized keratinocytes. They report that c-jun has five potential Gli binding sites in the promoter of the c-jun gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation